Methods of group exercise instruction - Kennedy, Carol A. 1958-; Yoke, Mary M. 1953- (Human Kinetics, 2014)
Explores the most common group of exercise modalities. This book highlights the commonalities of a variety of group exercise formats through training principles, correction and progression techniques, and safety tips to enhance the skills of both group exercise leaders and programme directors